(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 1994)
Renormalization transformations were introduced in statistical mechanics to study critical points. Their natural set-up, however, is within probability theory: they are maps between probability spaces, defined by suit.able probability kernels. We review several interesting questions motivated by applications in physics as well as in other areas like image processing and speech recognition.